1998
DOI: 10.1029/97jd02214
|View full text |Cite
|
Sign up to set email alerts
|

Fast time response measurements of HNO3 in air with a chemical ionization mass spectrometer

Abstract: Abstract. A chemical ionization mass spectrometer has been developed for fast time response measurements of HNO3 in ambient air. The apparatus was characterized in an informal intercomparison campaign at Green Mountain Mesa in Boulder, Colorado. Nitric acid was measured over a wide range of meteorological conditions. Detection limits of less than ! 5 pptv for a 1 s integration period were routinely obtained. The apparatus was sufficiently sensitive to measure ambient levels of HNO3 for all conditions except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 18 publications
1
69
0
Order By: Relevance
“…Heating the ion flow tube and ionizer slightly (80 • C) is suggested as a means to reduce surface adsorbed material. The addition of NH 3 to CIMS systems to reduce backgrounds in HNO 3 measurements, has been described by Huey et al (1998) and Neuman et al (2002), and was suggested as a solution to the high background of nitrate and perhaps other acid anions, since NH 3 appears to react with surface-adsorbed nitric acid to prevent it from desorbing into the gas phase. However, preliminary work by one of our co-authors (J.…”
Section: Application Of Ni-pt-cims To Ambient Air Measurementsmentioning
confidence: 99%
“…Heating the ion flow tube and ionizer slightly (80 • C) is suggested as a means to reduce surface adsorbed material. The addition of NH 3 to CIMS systems to reduce backgrounds in HNO 3 measurements, has been described by Huey et al (1998) and Neuman et al (2002), and was suggested as a solution to the high background of nitrate and perhaps other acid anions, since NH 3 appears to react with surface-adsorbed nitric acid to prevent it from desorbing into the gas phase. However, preliminary work by one of our co-authors (J.…”
Section: Application Of Ni-pt-cims To Ambient Air Measurementsmentioning
confidence: 99%
“…For scrubbing HNO 3 from ambient air we used a nylon filter, which has long been used as a medium to collect HNO 3 in filter measurements or as HNO 3 scrubber (Goldan et al, 1983;Huey et al, 1998) and has also shown in this study to effectively remove HNO 3 from the sample flow. For background measurements the sample air was branched off into an extra tubing with two vacuum-proof filter holders, the first containing a Teflon prefilter to remove particulate matter from the sampled air (Zefluor, pore size 1 µm, diameter 90 mm, Pall Gelman Corp.) and the second one containing a nylon filter (Nylasorb TM membrane disc filter, pore size 1 µm, diameter 90 mm, Pall Gelman Corp.).…”
Section: Background Measurements and Calibration Of Cimsmentioning
confidence: 99%
“…Several analytical techniques have been developed to measure gaseous HNO 3 in the troposphere, including nylon filter (Anlauf et al, 1988), mist chamber (Talbot et al, 1990), denuder technique (Perrino et al, 1990;Simon et al, 1995), luminol method (Hering et al, 1988), tunable diode laser spectroscopy (Horii et al, 2006), and chemical ionization mass spectrometry (CIMS) (Huey et al, 1998). Among the different approaches, the CIMS technique has the advantages of high sensitivity and fast time-response (Huey, 2007).…”
Section: Introductionmentioning
confidence: 99%